A Case of Heparin-Induced Thrombocytopenia That Developed in the Therapeutic Course of Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis - Taketoshi Nonaka; Makoto Harada; Masahiko Sumi; Wataru Ishii; Tohru Ichikawa; Mamoru Kobayashi (Case Reports in Rheumatology)
Background. Heparin-induced thrombocytopenia (HIT) causes thrombocytopenia via an immunological mechanism, resulting in severe organ injury due to arterial-venous thrombosis. HIT often develops in hemodialysis patients owing to heparin use. Anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) is a systemic vasculitis, and cases of AAV complicated with HIT are rare. In addition, it mostly occurs in patients undergoing hemodialysis. Case Presentation. An 87-year-old woman presented with rapidly progressive renal failure and severe leg edema. She was diagnosed with AAV and treated with glucocorticoid and heparin calcium to prevent deep vein thrombosis. Eight days after the start of heparin calcium, her platelet count decreased and the anti-platelet factor 4-heparin complex antibody was strongly positive (>5.0 U/mL; the cutoff point of the anti-platelet factor 4-heparin complex antibody evaluated by the latex turbidity assay is 1.0 U/mL). She was diagnosed with HIT and treated with argatroban. Subsequently, her platelet counts increased gradually. Conclusion. We encountered a case of HIT that developed prior to the induction of hemodialysis in the clinical course of AAV. When AAV clinical course presents thrombocytopenia, the possibility of HIT should be considered.